PGOT Social Service Center in the Delta Silicon Area of BekasiRegency with a Humanistic and Inclusive Architectural Approach - Kaysa Lihaldiany; Ari Rahadini; Andi Purnomo (Universitas Negeri Semarang, 2025)
The increasing number of people with social welfare problems (PMKS), particularly beggars, vagrants, and abandoned people (PGOT) in Bekasi Regency, which has a high urbanization rate, demands social service facilities that not only function as shelters but also provide holistic recovery and empowerment. The design of the PGOT Social Service Center in the Delta Silicon area of Bekasi Regency aims to create an environment that supports the social, psychological, and economic rehabilitation process for beneficiaries through the application of a Humanistic and Inclusive Architecture approach. This approach is realized through a humancentered design that prioritizes comfort, safety, and equal access for all users without discrimination. Inclusive principles are applied through universal design, such as the provision of easily accessible ramps and circulation, while humanistic values are embodied in the creation of a spatial atmosphere that encourages social interaction and empowers residents through skills training. The resulting design is expected to become a model for sustainable social facilities oriented towards human welfare.